Interaction of neuropeptide Y receptors (NPY1, NPY2 and NPY5) with somatostatin on somatostatin-induced feeding behaviour in neonatal chicken. Issue 1 (2nd January 2019) - Yousefvand, S.; Hamidi, F.; Zendehdel, M.; Parham, A.
ABSTRACT: 1. The present study was conducted to investigate whether brain somatostatin increases feed intake in neonatal chickens. The mediating role of neuropeptide Y receptors on feed intake induced by somatostatin was investigated. 2. In this study, seven experiments were designed, each with four treatment groups ( n = 44 in each experiment). In Experiment 1, chicks received control solution and 0.5, 1 and 2 nmol of somatostatin through intracerebroventricular (ICV) injection. In experiments 2, 3 and 4, chickens were ICV injected with control solution and 1.25, 2.5 and 5 μg of B5063 (NPY1 receptor antagonist), SF22 (NPY2 receptor antagonist) and SML0891 (NPY5 receptor antagonist), respectively. In experiment 5, 6 and 7 chickens received ICV injection of B5063, SF22, SML0891, with a co-injection of + somatostatin, control solution and somatostatin. The cumulative feed intake was measured until 120 min post injection. 3. Somatostatin significantly increased feed intake in FD3 chicks. Both B5063 and SML0891 dose-dependently decreased feed intake compared with the control group, while SF22 led to a dose-dependent increase in feed intake. In addition, the hyperphagic effect of somatostatin significantly decreased with co-injection of B560 plus somatostatin ( p < 0.05), but SF22 and SML0891 had no effect on feed intake induced by somatostatin in chicks ( p > 0.05). 4. Based on the results of this study, it is likely that somatostatin increased feed intake and NPY1 receptor acts as a mediator in hyperphagic effect of somatostatin in neonatal chicks.